Cryptocurrency investment adoption: an analysis of Indodax application acceptance using UTAUT2 - Anita Wulansari; Raffi Abdillah Putra Alisia; Rafika Rahmawati (Universitas Negeri Surabaya, Indonesia, 2026)
This study examines the determinants of cryptocurrency investment adoption through the Indodax application by extending the Unified Theory of Acceptance and Use of Technology 2 (UTAUT2). Specifically, it investigates the mediating role of performance expectancy in linking effort expectancy and trust to behavioral intention. Data were collected from 417 Indodax users in Indonesia and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that performance expectancy significantly influences behavioral intention, while effort expectancy and trust do not have significant direct effects. However, both variables indirectly influence behavioral intention through performance expectancy. This indicates that users prioritize expected benefits over ease of use and trust when making investment decisions in high-risk environments. This study extends UTAUT2 by demonstrating that, in high-risk fintech contexts, adoption behavior follows an indirect and sequential cognitive evaluation process. It provides empirical evidence from the Indonesian cryptocurrency market and highlights the conditional applicability of UTAUT2 in emerging digital investment ecosystems.